2002
DOI: 10.1002/hyp.332
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐variable parameter estimation to increase confidence in hydrological modelling

Abstract: Abstract:The expanding use and increased complexity of hydrological runoff models has given rise to a concern about overparameterization and risks for compensating errors. One proposed way out is the calibration and validation against additional observations, such as snow, soil moisture, groundwater or water quality. A general problem, however, when calibrating the model against more than one variable is the strategy for parameter estimation. The most straightforward method is to calibrate the model components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…In order to assess the model structure, the evaluation of a distributed model representing various processes should be done on each hydrological compartment it represents and at various scales (Refsgaard, 1997;Michaud and Sorooshian;1994;Bergström et al, 2002;Fortin et al 2001, Anderton et al 2002. As a single and integrative variable (i.e.…”
Section: N Varado Et Al: Evaluation Of the Rew Approach On The Dongmentioning
confidence: 99%
“…In order to assess the model structure, the evaluation of a distributed model representing various processes should be done on each hydrological compartment it represents and at various scales (Refsgaard, 1997;Michaud and Sorooshian;1994;Bergström et al, 2002;Fortin et al 2001, Anderton et al 2002. As a single and integrative variable (i.e.…”
Section: N Varado Et Al: Evaluation Of the Rew Approach On The Dongmentioning
confidence: 99%
“…Ambroise et al, 1995;Andersen et al, 2001;Khu et al, 2008;Dai et al, 2010). Bergström et al (2002) suggested that the model calibrated against more measured internal variables rather than streamflow only can greatly increase confidence in the physical relevance of the model. Vázquez et al (2008) adopted a multi-criteria protocol which included statistical, analytical and visual criteria to calibrate the model.…”
mentioning
confidence: 99%
“…The HBV light is a conceptual mode which is based on the HBV model [23]. It was coupled with a more detailed snow and glacier melt subroutine, employing the degree-day approach [24].…”
Section: Hydrologiska Byrans Vattenavdelning (Hbv) Modelmentioning
confidence: 99%
“…Rainfall and snowmelt (P) are divided into water filling the soil box and groundwater recharge depending on the relation between water content of the soil box (SM, in mm) and its largest value (FC, in mm) as shown in Equation (4). Actual evaporation from the soil box equals the potential evaporation if SM/FC is above LP (the threshold of Soil water content and Field water holding capacity), whereas a linear reduction is used when SM/FC is below LP, as shown in Equation (5) [23]. Groundwater recharge is added to the upper groundwater box (SUZ, in mm).…”
Section: Hydrologiska Byrans Vattenavdelning (Hbv) Modelmentioning
confidence: 99%